Novel synthesis of palladium (II) complexes derived from 3-arylsydnone-4-carbaldehyde N(4)-phenylthiosemicarbazones and biological activity. (25th October 2013) - Shih, Mei-Hsiu; Chen, Jian-Chyi; Lin, Guan-Ling; Lin, Tzu-Ting; Sun, Ming-Hsiang
Abstract: Objectives: The aim of this research is to investigate whether the oxygen atom O(6) in the sydnone ring of 3-arylsydnone-4-carbaldehyde N(4)-phenylthiosemicarbazones (HArSYTSCs, 3a–d) is a good electron donor atom upon metal complexation. Furthermore, ligands 3a–d and the corresponding palladium complexes (Pd(ArSYTSC)Cl, 4a–d) would be expected to find their potent biological activities. Methods: The desired palladium complexes 4a–d were first synthesized from thiosemicarbazones 3a–d. Then, the antiproliferative activity of ligands 3a–d and complexes 4a-d were tested against human hepatocellular carcinoma and human cervical epithelioid carcinoma (HeLa) cells by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl trazolium bromide (MTT) assay. Key findings: According to X-ray analyses, ligands 3a–d are bonded to the Pd (II) center in an O, N, S-tridentate coordination mode through sydnone carbonyl oxygen O(6), azomethine nitrogen and the thiolate sulfur atom. The carbonyl oxygen of the sydnone ring is found to be a good electron donor site upon metal complexation. Moreover, MTT assay results reveal that the palladium complexes 4a–d have greater antiproliferative activity than 5-fluorouracil. In particular, the complexes exhibit obvious better activity than the corresponding ligands 3a–d against HeLa cell. Conclusions: The results indicate that the synthesized novel palladium complexes have greater antiproliferative activity than both 5-fluorouracil and the corresponding ligands against HeLa cell. Accordingly, the study of sydnonyl complexes bearing anticancer activities may support the development of coordination chemistry.